Depression in Tuberculosis Patients and its Relationship to Socio Demographic Factors - Muhammad Munir Ahmed, Mahpara Mazhar, Arslan Zaidi (Journal of Rawalpindi Medical College, 2016)
Background: To study the prevalence of depression in tuberculosis patients and correlating it with various sociodemographic factors. Methods: In this observational study patients suffering from tuberculosis presenting to or already admitted in four tertiary care hospitals and TB Hospital of Rawalpindi were recruited consecutively and screened for depression. The severity of depression was assessed using Hamilton Rating scale for Depression. Results: Depression, in patients currently on treatment, was 49.4%. Out of whom 41.5% were mildly depressed, 34.1% were moderately depressed, 21.9% were severely depressed. Significant depression was evident in those living in rural setup( p= 0.038) and those falling in 46-60 years old category(p=0.042) Conclusion: Nearly half of the proportions of people seeking treatment for TB in tertiary care setup suffer from depression. Early diagnosis and treatment of depression in TB patients is essential.